Physiological recovery from the short-term training blocks and their acute response to sleep and heart rate variability - Viberg, T.; Aittokoski, T.; Ahtiainen, J. (19th International Symposium "Modern Science and Practice for Strength and Endurance Training" October 10-12, 2018, 2020)
To improve maximal endurance or strength performance, an optimal physiological training load is required. Post-exercise heart rate variability (HRV) has been shown to be a valid method to evaluate the training load 1,2. The main objective of this study was to determine whether the HRV and selective physiological indicators could assess cumulative metabolic and neuromuscular fatigue induced by the short-term high-intensity training blocks.